Law and Sacrifice in Aristophanes’ Birds - Fletcher, Judith (2015)
Jurisprudence is a prominent theme in Birds with such technical details that Ruschenbusch could supplement his inventory of Solonian law from Aristophanes’ text. Associated with the legal moments of the comedy is the ritual of sacrifice, which motivates the plot and frames its most important events. The relationship between these two cultural systems is hardly incidental, as Derrida recognized in his seminal essay, “Force of Law,” which connects carnivorous sacrifice with the authority to make law. This paper explores how Aristophanes’ Birds affirms a contiguity between law and sacrifice to establish Peisetaerus as the sole juridical power in Nephelococcygia. (Párrafo extraído a modo de resumen)